Khazanah Leksikon Tradisi Penangkapan Ikan Paus dalam Novel Suara Samudra Karya Maria Matildis Banda: Kajian Ekolinguistik - Widarsini, Ni Putu N. (Humanis, 2021)
This paper aims to find and analyze the forms and categories lexicon of the whale chathing tradition in the Suara Samudra novel by Maria Matildis Banda. To realize this, the library method and scrutinize met hod were applied in the data collection assisted with notes technical . And then, the data analyzed with qualitative description method and ecolinguistics theory. Then, the result showed with informal and formal method. The result showed that forms and categories lexicon of  the whale  chathing tradition in the Suara Samudra novel by Maria Matildis Banda writed with lexicon of Lamalera language. That the lexicon consist (1) biotic lexicon, like koteklema ‘whale’, lamafa ‘stab fisherman of whale’, and matros ‘paddle fisherman of boat’; and (2) abiotic lexicon, like peledang ‘boat’, kerakki ‘special chair of stab fisherman of whale in the boat’, and blettu ‘traditional hat from palm leaves’. The form of lexicon consist (1) singular form, like buri ‘trumpet from skin of shell’ and kela ‘place of ball of twine yarn’; (2) complex form, like lama uri ‘special fisherman for drive boat’ and tena laja ‘sailing boat’. The cathegory of lexicon consist noun and noun phrase.